Entre a ausência e a presença : o papel da rasura na transformação de significado - Ferreira, Margarida Lemos, 1991- (2018)
Link para Video - https://drive.google.com/file/d/1dSOa2z3tu_vBaX3p0W7a8ZiJ__uUEAuX/view?usp=sharing